Anti-Aging Potential of Moringa oleifera Bioactive Compounds: A Molecular Docking Approach Targeting Sirtuin Proteins - Marthin, Jeffrey; Noverita, Noverita; Prasasty, Vivitri Dewi (Universitas Nasional Jakarta, 2025)
Moringa oleifera has long been valued in traditional skincare, but its molecular interactions with key aging regulators remain poorly understood. This study elucidates the anti-aging potential of Moringa oleifera bioactive compounds through their modulation of sirtuin proteins (SIRT2, SIRT5, SIRT6), which govern genomic stability and oxidative stress responses. Using computational approaches, we performed molecular docking simulations (AutoDock Vina) on 20 bioactive compounds against sirtuin crystal structures from the Protein Data Bank. Comparative analysis with commercial anti-aging agents (niacinamide, AHA, ceramide) identified three Moringa compounds with superior binding affinities: rutin (-10.7 kcal/mol), quercetin (-8.9 kcal/mol), and chlorogenic acid (-7.9 kcal/mol), all outperforming niacinamide (-6.1 kcal/mol). SwissADME profiling confirmed their drug-like properties, including high oral bioavailability, blood-brain barrier penetration, and minimal toxicity risks. Mechanistically, these compounds demonstrated dual antioxidant and anti-inflammatory capacities, suggesting synergistic protection against oxidative damage and inflammation-driven aging. Our results position Moringa oleifera as a rich source of multitarget anti-aging candidates, combining computational validation with biological relevance to advance natural product-based interventions against cellular senescence.